Amino Acid Transport and Metabolism in Myeloid Function - Halaby, Marie Jo; McGaha, Tracy L. (Frontiers in Immunology, 2021)
Regulation of amino acid availability and metabolism in immune cells is essential for immune system homeostasis and responses to exogenous and endogenous challenges including microbial infection, tumorigenesis and autoimmunity. In myeloid cells the consumption of amino acids such as arginine and tryptophan and availability of their metabolites are key drivers of cellular identity impacting development, functional polarization to an inflammatory or regulatory phenotype, and interaction with other immune cells. In this review, we discuss recent developments and emerging concepts in our understanding of the impact amino acid availability and consumption has on cellular phenotype focusing on two key myeloid cell populations, macrophages and myeloid derived suppressor cells (MDSCs). We also highlight the potential of myeloid-specific of amino acid transporters and catabolic enzymes as immunotherapy targets in a variety of conditions such as cancer and autoimmune disease discussing the opportunities and limitations in targeting these pathways for clinical therapy.